2014
DOI: 10.5219/328
|View full text |Cite
|
Sign up to set email alerts
|

Examination of heat treatments at preservation of grape must

Abstract: Heat treatment is a well-known process in food preservation. It is made to avoid and to slow down food deterioration. The process was developed by Louise Pasteur French scientist to avoid late among others wine further fermentation. The different heat treatments influence the shelf life in food production. In our article we present the process of grape must fermentation, as grape must is the base material of wine production. The treatment of harvested fresh grape juice has a big influence on end product qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…Based on the comparative studies, it was found that based on the increase in CO2 concentration that represents the fermentation process, the heat treatments delayed the fermentation process in all cases. But there was no detectable difference between the effect of microwave and convective heat treatment methods in this study either (KORZENSZKY -MOLNÁR 2014).…”
Section: Discussioncontrasting
confidence: 60%
“…Based on the comparative studies, it was found that based on the increase in CO2 concentration that represents the fermentation process, the heat treatments delayed the fermentation process in all cases. But there was no detectable difference between the effect of microwave and convective heat treatment methods in this study either (KORZENSZKY -MOLNÁR 2014).…”
Section: Discussioncontrasting
confidence: 60%
“…In the case of berries, raw fruits are sufficient, so heat treatment is rare. Heat treatment is a known process in food preservation that prevents and slows spoilage [27]. Therefore, blackcurrant has the disadvantage of being easily fermented due to its high sugar content, so heat treatment was performed on blackcurrant in consideration of various experimental methods.…”
Section: Hplc Chromatograms Of Quercetin-3-o-glucuronide From Blackcurrantmentioning
confidence: 99%
“…The possibility of microwave pasteurization has been a determining field of research conducted by a team at the Faculty of Mechanical Engineering, Szent Istv an University (formerly G€ od€ oll} o University of Agricultural Science) for nearly 20 years. The feasibility of microwave heat treatment as well as its energy-saving and technological advantages are proved (Sembery & G eczi, 2008;G eczi & Sembery, 2010;Garnacho et al, 2012;G eczi et al, 2013a;G eczi et al, 2013b;Korzenszky et al, 2013;Korzenszky & Moln ar, 2014). Their research covers the heat treatment of fresh milk immediately after milking and the continuous fermentation of fruit juice (apple, orange juice, grape must) in order to increase the shelf life as well as to improve the quality of liquid products.…”
Section: Introductionmentioning
confidence: 99%